Effect of Leadership on Employee Performance in Rwanda Revenue Authority (International Journal of Scientific Research and Management (IJSRM), 2024)
The general objective of this research study was to assess the Effect of leadership on employee performance in Rwanda Revenue Authority. The study used a multiple linear regression model. This study used a descriptive research design since it provides a researcher with first-hand primary data that is collected, maintained, and analyzed for the research goals. The current research was compassed by the following specific objectives: To establish the effect of leadership personality on employee performance at Rwanda Revenue Authority; To examine the effect of leadership styles on employee performance at Rwanda Revenue Authority; To analyze the effect of leaders’ competency on employee performance at Rwanda Revenue Authority; To analyze the influence of leaders’ commitment on employee performance at Rwanda Revenue Authority. The target population in this study was 1248 who are staff at Rwanda Revenue Authority (RRA). The researcher used purposive sampling. The sample size of the study was 269 Rwanda Revenue Authority staff selected from the known population of 1248 staff. Simply, in this study data was collected from both primary and secondary sources. The researcher distributed 269 questionnaires to the respondents, however, 265 respondents submitted in their responses while 4 respondents did not submit their responses. 56.2% of respondents strongly agreed that Leaders at RRA are considerate when dealing with subordinates which motivate staff to work and meet deadlines, 31.7% agreed with the statement, none of respondents were undecided, and 8.7% disagreed with the statement while 3.4% strongly disagreed with the statement. About the second item, 25.7% of respondents strongly agreed that Leaders at Rwanda Revenue Authority live a life of integrity at work and outside work which ignites workers to provide a quality work; 27.9% agreed with the statement, 14.7% were undecided, 24.2% disagreed with the statement while 7.5% strongly disagreed with the statement. 62.3% agreed with the statement that leaders at RRA use transformational leadership style to assist employees meet deadlines, 3.8% of respondents were undecided, and 32.8% disagreed with the statement while 1.1% strongly disagreed with the statement. Moreover, 12.1% of respondents strongly agreed that Transactional Leadership is used in Rwanda Revenue Authority by Leaders and have contributed to Quality of work; 86.8% agreed with the statement, none of respondents were undecided, 1.1% disagreed with the statement and none of respondents strongly disagreed with the statement. 63.8% agreed with the statement that leaders at RRA exhibit work expertise which makes also employees to excel in meeting deadlines, none of respondents were undecided, and 11.7% disagreed with the statement while 23.8% strongly disagreed with the statement. Likewise, 32.5% of respondents strongly agreed that Leaders at Rwanda Revenue Authority are results oriented which also encourages all employees to strive for achieving departmental goals; 67.5% agreed with the statement, none of respondents were undecided, none of respondents disagreed with the statement and none of respondents strongly disagreed with the statement. The researcher used questionnaire as data collection instrument. SPSS version 23.00 (Statistical Package for Social Scientists) was used to analyze the coded data.